Strategi Pengawasan Kepala Sekolah Dalam Membangun Pendidikan Karakter Pada MIS Guppi 12 Lubuk Kembang - Effendi, Mardian; Warlizasusi, Jumira; Harahap, Emmi Kholillah (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2023)
This research aims to explore and analyze the implementation of character education strategies in Madrasah Ibtidaiyah (MIS) Guppi 12 Lubuk Kembang. The research method employed a qualitative approach with a case study design. Data were collected through participatory observation, semi-structured interviews, and document analysis, focusing on classroom dynamics, extracurricular activities, and documents related to the character education program. The results of the study indicate that the school principal and the character development team successfully integrated character values into the curriculum and extracurricular activities. Support and training provided to teachers through a reward system also proved effective in motivating students. Regular monitoring and evaluation support continuous improvement, creating a profound learning environment. This research contributes to a better understanding of character education practices at the Madrasah Ibtidaiyah level and provides a foundation for the development of more effective strategies in the future.